Carbon fixation by basalt-hosted microbial communities - Orcutt, Beth N.; Sylvan, Jason B.; Rogers, Daniel; Delaney, Jennifer; Lee, Raymond W.; Girguis, Peter R. (Frontiers in Microbiology, 2015)
Oceanic crust is a massive potential habitat for microbial life on Earth, yet our understanding of this ecosystem is limited due to difficulty in access. In particular, measurements of rates of microbial activity are sparse. We used stable carbon isotope incubations of crustal samples, coupled with functional gene analyses, to examine the potential for carbon fixation on oceanic crust. Both seafloor-exposed and subseafloor basalts were recovered from different mid-ocean ridge and hot spot environments (i.e., the Juan de Fuca Ridge, the Mid-Atlantic Ridge, and the Loihi Seamount) and incubated with 13C-labeled bicarbonate. Seafloor-exposed basalts revealed incorporation of 13C-label into organic matter over time, though the degree of incorporation was heterogeneous. The incorporation of 13C into biomass was inconclusive in subseafloor basalts. Translating these measurements into potential rates of carbon fixation indicated that 0.1 – 10 nmol C g-1rock d-1 could be fixed by seafloor-exposed rocks. When scaled to the global production of oceanic crust, this suggests carbon fixation rates of 10^9 – 10^12 g C yr-1, which matches earlier predictions based on thermodynamic calculations. Functional gene analyses indicate that the Calvin cycle is likely the dominant biochemical mechanism for carbon fixation in basalt-hosted biofilms, although the reductive acetyl-CoA pathway and reverse TCA cycle likely play some role in net carbon fixation. These results provide empirical evidence for autotrophy in oceanic crust, suggesting that basalt-hosted autotrophy could be a significant contributor of organic matter in this remote and vast environment.